2018
DOI: 10.1111/nph.15574
|View full text |Cite
|
Sign up to set email alerts
|

Lipo‐chitooligosaccharide signalling blocks a rapid pathogen‐induced ROS burst without impeding immunity

Abstract: Summary Molecular signals released by microbes at the surface of plant roots and leaves largely determine host responses, notably by triggering either immunity or symbiosis. How these signalling pathways cross‐talk upon coincident perception of pathogens and symbionts is poorly described in plants forming symbiosis. Nitrogen fixing symbiotic Rhizobia spp. and arbuscular mycorrhizal fungi produce lipo‐chitooligosaccharides (LCOs) to initiate host symbiotic programmes. In Medicago truncatula roots, the percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 46 publications
(72 reference statements)
1
17
1
Order By: Relevance
“…5c), a PR10 and a chitinase, revealed that co-treatment with Sm LCO inhibited CO8 induction of these genes (Fig. 5c), in disagreement with a recent report 56 . The combination of LCOs and COs inhibits defense-related gene expression, but these two signals act synergistically to enhance the degree of symbiotic gene expression, as measured using qRT-PCR of Vapyrin and HA1 (Fig.…”
Section: Resultscontrasting
confidence: 83%
“…5c), a PR10 and a chitinase, revealed that co-treatment with Sm LCO inhibited CO8 induction of these genes (Fig. 5c), in disagreement with a recent report 56 . The combination of LCOs and COs inhibits defense-related gene expression, but these two signals act synergistically to enhance the degree of symbiotic gene expression, as measured using qRT-PCR of Vapyrin and HA1 (Fig.…”
Section: Resultscontrasting
confidence: 83%
“…Possibly linked to their roles as symbiotic signals, LCOs can interfere with immunity-related signaling in legumes (Rey et al, 2019) and suppress innate immune responses, even in the nonmycorrhizal plant Arabidopsis thaliana (Liang et al, 2013). How LCOs dampen legume immunity is still unclear as they can also induce defense gene expression (Nakagawa et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Cu, Fe) to rhizobia housed in symbiosomes and thus influence N‐fixation (Senovilla et al , 2018; Lui et al , 2020). Similarly, recent papers highlight the complex crosstalk between legume immunity and rhizobial symbiosis (Berrabah et al , 2018; Rey et al , 2019; Sorroche et al , 2019).…”
Section: What Are Your Favourite New Phytologist Papers Of Recent Years and Why?mentioning
confidence: 96%